Compliance as an economic category - Sikorska, Małgorzata; Veres Somosi, Mariann; Pererva, P. G. (Київський національний університет культури і мистецтв, 2018)
Compliance with laws, regulations and standards in the field of compliance usually refers to issues such as compliance with appropriate standards of market conduct, management of conflicts of interest, fair treatment of clients and ensuring a fair approach in advising clients.
Keywords: economic category; risk; industrial enterprises